Analisa Pengaruh Aspek-Aspek Ruhiyyah Terhadap Minat Penanaman Modal Nasabah Study Kasus Bmt Bintoro Madani - Hadiyanto, Akhmad; , Dr, Hidayat Nataatmadja (2015)
BMT Bintoro Madanis hoped to be usefull for its surrounding, Phisicily, the building or BMT Bintoro Madani 's office is tried to reflect a sheitered frienship and having harmony with its surrounding. Socially the working programme the working of BMT Bintoro Madani employees should be able to create a good people, such to arrange a meeting and deepen Alqur 'an, periodically with the member of the office or the people of the BMT's surrounding, or to commemorate the Islam day on BMT Bintoro Madani 's environment.This study have had some objective as follow : 1.To give a picture of micro-financial institution as a shape of of financial institutions of village establisment system which is based on "Balaiusaha Mandiri Terpadu (BMT) in a country which has proble ms in getting a trustment from the creditur institutions whether institutionally or individually. 2.To help in pioneering the establishment of the micro-financial institutions(LKM) in this case especially the objective of this study is to find some ways in controlling and evaluating which is based on the result of the institution work, in line with the value of the credibleinstitutions healthy. 3.To find some strastegic ways which can support the BMT institution, especially in controlling ang evaluating based on the institution work. 4. To find the effective ways to increase the lawyer 's trust to collect the capital and to make go out the cost, to increase the workers opportunity and develop the house - industry. The continuously of BMT institution and it can fun ctioning well which has developed about 10.000 institution in Indonesia, as institution which support the economic activities of micro - industry, small and middle - industry is made by the reaching formulations of the BMT healthy level. So it can give whether for the institution itself or the lawyer. Based from that illustration which is possible done by other BMT institution in whole Indonesia ini facing the same problems. So the advantage of this study which are done for analyzing the working of BMT Bintoro Madani welfare are as follows : 1.Tobe able in analyzing the BMT 's participation which is as an institution connected between the owner who save their money in the institution with the micro business which need capital to develope this industry (effort). It can also be used by another BMT in Indonesia for looking for themselves about the function itself. 2.To analyse BMT participation as an institution to give an opportunity than is usefull for the owner and the micro anf small even middle-industry 3.To be able in giving an illustration about the opportunity in increasing the effort's skill for the small and middle-industry by doing the erection pattern and the approximation of Muamalah institution. 4.Tobe able in giving consideration in making fund to increase communications as information and to promote the product from the micro, small and middle-industry. 5.To participate in finding and introducing the technology, so It can increase the additional value of micro, small ang middle-industry. 6.To limit the social differentiation between the member and the society. 7.To be able to practice in reality life between "UBUDIAH" religious ang Muamalah religious. A poor BMT shows that there are some mistake in managing not only in management sector, in institutionally but also in moeslem law. If it didn't anticipate, the BMT institution would face many difficulties in doing their business. And in the end, it would be sink ang have a loss. Beside it can also make negative value for the institution and the axistance of BMT and generally for the mouslem financial institution in tht society. Remembering that the financial institution is as must service which is easy with information that involves of managing the BMT institution pattern in Indonesia.